TINJAUAN HUKUM BUNGA BANK PERSPEKTIF ULAMA’ DAN ORGANISASI KEISLAMAN - Armawi (KASBANA, 2025)
Bank interest legality is a contemporary dilemma in Islam. While classical riba is universally prohibited , bank interest is intensely debated regarding its classification as riba. The controversy intensified with MUI's 2003 fatwa prohibiting it, though some still consider it permissible. To comprehensively examine scholars' and Islamic organizations' views on bank interest law and its relation to riba. Research Method: This is a library research study using primary and secondary data, analyzed through reduction, presentation, and conclusion drawing. Findings: Significant differences in opinion exist. Gus Baha and Syekh Turaichan Kudus distinguish bank interest from riba and permit it, considering economic stability and currency devaluation. Yusuf Al-Qardhawi strictly prohibits bank interest, classifying it as riba and a cause of global crises. Mohammad Sayyid Thanthawi argues bank interest is not forbidden, differing from coercive pre-Islamic riba due to consent and information in current transactions. NU's fatwa reflects three stances: absolute prohibition, permissibility, and syubhat (doubtful). Keywords: Riba, Bank Interest, Gus Baha, Yusuf Al-Qaradhawi